Aplikasi Security Camera Untuk Mobil Berbasis Android Dan Raspberry Pi - Endhy, Kezia Tiatira; Noertjahyana, Agustinus; Handojo, Andreas (Jurnal Infra, 2018)
Based on the data of Polda Metro Jaya, theft of four-wheel motor vehicles experienced the highest increase which is 17 percent in 2015. Nowadays, the perpetrators are increasingly skilled in running a car theft. Despite having a car alarm for security system, it has limited distances. It leads to many unexpected ways for the perpetrators to damage on the car security system.It is certainly dangerous if the car owner left the car in a long distance without monitoring. In addition, the owner of the car will be aggrieved. Hence, it is necessary to build a technology that can help car owners to monitor the vehicle remotely. Regarding the problem above, an application that can help car owners to check their vehicles anywhere is required.Security Camera application uses Android and Raspberry Pi. This application is able to detect the movement of the camera in which is connected with the Raspberry Pi. In addition, the users can view an in-car live streaming. Moreover, the users will get notifications on their android devices and email as well as get an access to images and videos in which is detected in the camera. Therefore, this application will be able to help the users to check the situation surrounding their car as a protection from theft crime.